Go/no-go task performance of Japanese children: Differences by sex, grade, and lifestyle habits - Shikano, Akiko; Noi, Shingo (Frontiers in Public Health, 2022)
Background: Japanese children face critical psychological challenges that urgently need to be addressed. Objective: This study aimed to clarify performance differences in go/no-go tasks among Japanese elementary and junior high students by sex and grade and comprehensively investigate the relationship between children’s lifestyle habits and performance. Methods: In total, 4,482 (2,289 males, 2,193 females) 1st grade elementary to 3rd grade junior high students (6–15 years old) participated. We conducted a survey and the go/no-go experiments in the participating schools on weekday mornings from November 2017 to February 2020. We collected data on the number of errors in the go/no-go tasks in response to visual stimuli (commission errors in the no-go tasks; omission errors in the go tasks); and on lifestyle habits (i.e., sleep, screen time, and physical activity) using questionnaires. Results: For the commission errors, the results demonstrated differences by sex and grade; for the omission errors, differences were only observed by grade. Additionally, we analysed the relationship between both types of errors and sex, grade, sleep conditions, screen time, and physical activity using binomial logistic regression analysis. Commission errors were significantly related to sex and grade whereas omission errors were related to grade, bedtime, screen time, and physical activity. Conclusions: Our results highlighted that children’s cognitive functions are related to their lifestyle habits (i.e., sleep conditions, screen time, and physical activity) in addition to sex and grade.